(untitled) (Revista Sistemas de Producción Agroecológicos, 2021)
Currently, agricultural producers have a predilection for sheep production systems, due to their great variability in production and demand, since these animals obtain meat, milk, wool and genetics, which is why research with this species. They have a productive value for the guild. However, it is known that nutrition is one of the most basic and important aspects that must be taken into account in a production and that digestibility values ​​have monetary implications for the profitability of these producers. This is how this research seeks to analyze and compare the nutritional quality and digestibility in vivo of 3 different food sources, the grass known as King grass (Pennisetum purpureum), the (Tithonia diversifolia), known as Boton de oro in Colombia, and a silage made with King grass, molasses and Wheat bran, in 3 Creole sheep. The study was carried out in the farm of the University of Los Llanos, Barcelona neighborhood, located at kilometer 12 way to Puerto López (Villavicencio, Meta). Each of the sheep was feed with only one type of food for 6 days, where an adaptation period of 3 days and a data collection of the next 3 days was made. After this, on the seventh day a stool sample was taken to the oven in order to estimate its digestibility coefficients and energy distribution. In this, the nutritional value and digestibility coefficients of crude fiber (FC), dry matter (MS), raw protein (PC) and fat (GR) were determined. In addition, the non-nitrogenous extract (NNS), the percentage of total digestible nutrients (NDT), gross energy (EB), digestible energy (ED) and metabolic energy (MS) were estimated. From these data, analyzes were carried according to the theory and the comparison of the data, it is in this way that it was concluded that the food with the best nutritional results, of the three foods, was the Botón de oro (Tithonia diversifolia) and that in. In general the three foods are of good quality when compared to the theory.